Interpoems Journey of a Protagonist: Zbigniew Herbert and “Mr. Cogito” - Nevra VARDAL ATAK (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2018)
The book "Mr. Cogito", which was published in 1974, is regarded as a turning point in the poetry of Zbigniew Herbert, who is one of the most important figures of Polish poetry in the twentieth century. Through the book's eponymous character Mr. Cogito, the poet deals with more personal and actual topics. In this context, Mr. Cognito is assumed to be Herbert's lyrical mask or his alter ego. This lyrical subject, who for the first time emerged in Herbert's fifth book, continued his existence till the poet's last poetry volume. In the course of time, the reader witnesses the changes of Mr. Cogito. On the one hand, he evokes the Everyman type with his interest in ordinary issues, his ridiculous aspects, ironic approaches and his image as he wanders around the suburbs, while on the other, he draws the image of a modern philosopher with deep thoughts on philosophy, art and aesthetics. Mr. Cogito, who is both closely related to pop culture and classical art, a man who thinks, observes and who is curious, also reveals Herbert's versatile personality. In this study, starting from the first book, Herbert's fictional hero Mr. Cogito is examined in different ways and his relationship between the poet is pointed out.